Simulation as a planning tool for job-shop production environment - Maram, Venkataramana; Mohd Nawawi, Mohd Kamal; Abdul Rahman, Syariza; Sultan, Sultan Juma (2015)
In this paper, we made an attempt to use discrete event simulation software ARENA® as a planning tool for job shop production environment.We considered job shop produces three types of Jigs with different sequence of operations to study and improve shop floor performance.The sole purpose of the study is to identifying options to improve machines utilization, reducing job waiting times at bottleneck machines.First, the performance of the existing system was evaluated by using ARENA®. Then identified improvement opportunities by analyzing base system results.Second, updated the model with most economical options.The proposed new system outperforms with that of the current base system by 816% improvement in delay times at paint shop by increase 2 to 3 and Jig cycle time reduces by Jig1 92%, Jig2 65% and Jig3 41% and hence new proposal was recommended.